Depression and disease progression in amyotrophic lateral sclerosis: A comprehensive meta-regression analysis. (August 2015) - Pagnini, Francesco; Manzoni, Gian Mauro; Tagliaferri, Aurora; Gibbons, Chris J
Depression in people with amyotrophic lateral sclerosis, a fatal and progressive neurodegenerative disorder, is a serious issue with important clinical consequences. However, physical impairment may confound the diagnosis when using generic questionnaires. We conducted a comprehensive review of literature. Mean scores from depression questionnaires were meta-regressed on study-level mean time since onset of symptoms. Data from 103 studies (3190 subjects) indicate that the Beck Depression Inventory and, to a lesser degree, the Hospital Anxiety and Depression Scale are influenced by the time since symptom onset, strongly related to physical impairment. Our results suggest that widely used depression scales overestimate depression due to confounding with physical symptoms.